Prospective associations between childhood externalising and internalising problems and adolescent alcohol and drug use: The Bergen Child Study. Issue 5 (October 2018) - Heradstveit, Ove; Skogen, Jens Christoffer; Bøe, Tormod; Hetland, Jørn; Pedersen, Mads Uffe; Hysing, Mari
Aims: The literature on associations between internalising problems and subsequent alcohol/drug use and problems shows mixed results, and it is important to consider different aspects of internalising problems along with co-occurring externalising problems. Methods: In a longitudinal study ( n = 2438) followed up when the subjects were 7–9, 11–13, and 16–19 years of age, we investigated associations between parent/teacher-reported externalising and internalising problems (Strengths and Difficulties Questionnaire, SDQ) and adolescent self-reported alcohol and illicit drug use and problems. Socioeconomic status (SES), gender, and age were included as potential confounding variables. We also adjusted for the potential confounding effects from externalising problems on the association between internalising problems and alcohol/drug use, and vice versa. Results: Externalising problems were positively associated with all measures of alcohol/drug use and problems (adjusted odds ratios [ AOR s] ranging from 1.24 to 1.40, all p < .05), while internalising problems were negatively associated with all measures of alcohol/drug use ( AOR s ranging 0.83 to 0.88, all p < .05). Full-scale SDQ externalising problems were somewhat stronger and more robust predictors of adolescent alcohol/drug-related problems compared with SDQ externalising subscales, while only full-scale SDQ internalising problems were negatively associated with alcohol/drug-related problems. All estimates were similar across genders. Conclusions: Childhood externalising problems are positively associated while internalising problems are negatively associated with alcohol/drug use and problems in late adolescence.